Maximizing blue water use efficiency of wheat (Triticum aestivum) through irrigation and mulching - MADHU, M; ADHIKARY, PARTHA PRATIM; JAKHAR, PRAVEEN; DAS, N K; BARLA, G W (The Indian Journal of Agricultural Sciences, 2019)
A field study was conducted in sub-humid Eastern Ghats region of India to investigate the effect of different soil moisture conservation practices, viz. no-mulch (NM) as a control, ridge and furrow (RF), Gliricidia mulch (GM) and Lantana mulch (LM) on water productivity, and yield of wheat (Triticum aestivum L.) under three levels of irrigation (CPE100 = 100%, CPE80 = 80% and CPE60 = 60% ). Total water use by wheat was 270.1–365.6 mm during 2016–17 and 210.4–302.5 mm during 2015–16. Averaging both years, wheat used was 88.35 mm (26.8%) and 44.9 mm (13.6%) more water at CPE100 over CPE60 and CPE80, respectively. Among the irrigation levels, higher water productivity (WP) was observed in CPE60 (13.6, 9.8 kg/m3) compared to CPE80 (12.8, 9.3 kg/m3) and CPE100 (11.3, 8.9 kg/m3) for both years, respectively. CPE60 resulted in 5.9 and 15.8% greater WP over CPE80 and CPE100, respectively. Mulching increased WP by 27.8% in GM and 23.3% in LM treatments compared to NM. Irrigation with mulching treatments, CPE60 + GM exhibited WP of 15.9 and 14.7 kg/m3, and CPE60 + LM WP of 11.0 and 10.6 kg/m3 during 2015–16 and 2016–17, respectively. On an average, mulching treatment produced additional total WP of 2.2–2.6 kg/m3, green WP of 0.5–0.7 kg/m3 and blue WP of 1.7–2.0 kg/m3 over NM. Thus CPE80+ GM could be successfully applied during post-monsoon (Rabi) season in wheat production allowing a water savings of 20% without any yield loss.